The management communication on Shari'ah compliance : the Case of Malaysian takaful operators' (TOS) - Hafiza binti Harun (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
Shari'ah governance organs within any Islamic Financial Institutions are profoundly accountable to ensure the compliance to the requirement of Islamic principles. Management is one of the key governance organs who are expected to integrate Shar'ah governance considerations in business and risk strategies as well as promoting a Sharī'ah compliant culture within their institution. Under the supervisory and regulatory jurisdiction of Bank Negara Malaysia, Takaful is subject to comply with this requirement. The discovery on how management adheres to the relevant regulations and espouses the organizational culture is worth to be assessed. Therefore, the aims of this study are to assess the management's assurance of compliance to the relevant regulations and examine the organizational cultures and values adopted by Malaysian Takaful operators. The assessment on the contributing factors towards effective management communication has also been focused to complement the accuracy of the study. Semi-structured interview method was administered involving 11 Malaysian Takaful operators. The findings show that Malaysian Takaful operators are observant to the Sharī'ah, regulatory and compliance requirements at all times. The overall culture that shapes Malaysian Takaful operators internally is universal values which are not against Sharī'ah principles. The management is also expected to adopt excellent top-down communication skills which is crucial for Malaysian Takaful operators' growth and sustainability. Most significantly, this study serves as a material reference to other Islamic Finance sectors in assessing the effectiveness of management communication of Sharī'ah compliance to other organs in Sharī'ah Governance Framework. Accordingly, this finding facilitates the Regulator in formulating a comprehensive parameter strengthening the role and function of management as one of the key organs of Sharī'ah Governance.